2014
DOI: 10.1158/1055-9965.epi-14-0249-t
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insulin-Related Serum Factors with Colorectal Polyp Number and Type in Adult Males

Abstract: Background Dysregulated insulin signaling is thought to contribute to cancer risk. Methods To determine if insulin-related serum factors are associated with colon polyps, 126 asymptomatic men (48–65yr) were recruited at colonoscopy. Blood was collected. Odds ratios were determined using polytomous logistic regression for polyp number and type. Results Males with serum C-peptide concentration >3.3 ng/ml were 3.8 times more likely to have an adenoma relative to no polyp than those with C-peptide ≤1.8 ng/ml. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Our study identified associations of IFN-α2, IL-10, MCP-3, MDC, IL-7 and IL-8 with colorectal polyps. Additionally, TNF-α, IP-10 and VEGF have been previously reported to be associated with colorectal polyps in this population (Comstock et al, 2014a; Comstock et al, 2014c). Therefore, data from the current study population supports that of other studies analyzing serum cytokines in cases of colorectal neoplasia.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our study identified associations of IFN-α2, IL-10, MCP-3, MDC, IL-7 and IL-8 with colorectal polyps. Additionally, TNF-α, IP-10 and VEGF have been previously reported to be associated with colorectal polyps in this population (Comstock et al, 2014a; Comstock et al, 2014c). Therefore, data from the current study population supports that of other studies analyzing serum cytokines in cases of colorectal neoplasia.…”
Section: Discussionmentioning
confidence: 69%
“…Some details about this study population have recently been published (Comstock et al, 2014a; Comstock et al, 2014b; Comstock et al, 2014c). Briefly ( Table 1 ), 57 (45%) of the 126 participants had at least one polyp.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking status was assessed as “ever smoked” or “never smoked”. Each individual received a full colonoscopy as previously described (14). Serum and plasma fractions were separated from blood and stored at −80° C.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, an increased risk associated with baldness was virtually confined to adenomas of small size, tubular histology, and/or 1–2 adenomas. Interestingly, in a recent study that examined insulin-related serum markers in relation to types of CRA in Caucasian males, circulating C-peptide, a marker of insulin secretion, was strongly associated with tubular adenomas (OR comparing extreme tertiles, 3.8; 95% CI, 1.3–11.2) ( Comstock et al , 2014 ). Thus, the insulin pathway may be particularly relevant to linking baldness to tubular adenomas and, indeed in our study, a positive association was suggested for large or multiple adenomas if they are of tubular histology.…”
Section: Discussionmentioning
confidence: 99%